The Impact of Kahoot Application on Students’ EFL Learning Achievement - Hasyim, Ruslan; Munawir, Andi; A, Yuliana; Fatma, Fatma; Sulviana, Sulviana; A, Nasrullah; Sultan, Eva Lestari (Corolla International Conference, 2026)
This study aims to determine the impact of the game-based learning application Kahoot on the academic performance of students at Junior High School in Sorong during their English as a Foreign Language (EFL) classes. This research employs a quantitative, pre-experimental, one-group research design. The population for this study consists of students with Class VIII K, totalling 30 students as the sample. The study utilizes pre-tests and post-tests as research instruments. Data collection techniques include administering pre-tests and gathering post-test results. Data analysis was conducted using SPSS. The results obtained from the SPSS tests demonstrate that the T-test indicates the acceptance of H1 and the rejection of H0. The analysis shows a significant improvement, with the average score increasing from 54.67 to 80.5, reflecting an improvement of 28.66%. The study included descriptive statistics, normality tests (with results of 0.189 and 0.120, indicating normal distribution), homogeneity tests, and T-tests. The T-test confirmed the acceptance of hypothesis H1, with a significance value greater than 0.05, indicating a statistically significant impact of game-based learning interventions on students’ academic performance. Thus, the findings of this study suggest that the use of game-based learning applications positively affects academic students’ performance.